2017
DOI: 10.3389/fimmu.2017.01059
|View full text |Cite
|
Sign up to set email alerts
|

Age-Stratified T Cell Responses in Children Infected with Mycobacterium tuberculosis

Abstract: Tuberculosis (TB) in young children differs from adult TB in that the risk of rapid progression to active TB (aTB) is higher in children than in adults. The reasons for this increased risk are not fully understood. Early differentiation remains difficult between children at risk to develop aTB from those who will remain healthy and develop a latent TB infection (LTBI). Biomarkers to differentiate aTB from LTBI in children, especially in very young children, are urgently needed. To identify M. tuberculosis-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…In addition 1,507 healthy controls or other controls were included. The majority of studies were in adults only (24/34, 70%;) ( 18 , 20 , 21 , 23 27 , 29 32 , 35 , 36 , 38 , 39 , 42 , 45 51 ), 8/34 (24%) studies were done in adults and children ( 19 , 22 , 28 , 37 , 40 , 41 , 43 , 44 ) and 2/34 (6 %) were done in children only ( 33 , 34 ). Outcomes were measured using enzyme-linked immunosorbent assay (ELISA), enzyme-linked immuno-spot assay (ELISPOT) and flow cytometry (FCM) in 27, 6 and 12 studies, respectively (Table 1 ), and some studies used several different assays for outcome measurement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition 1,507 healthy controls or other controls were included. The majority of studies were in adults only (24/34, 70%;) ( 18 , 20 , 21 , 23 27 , 29 32 , 35 , 36 , 38 , 39 , 42 , 45 51 ), 8/34 (24%) studies were done in adults and children ( 19 , 22 , 28 , 37 , 40 , 41 , 43 , 44 ) and 2/34 (6 %) were done in children only ( 33 , 34 ). Outcomes were measured using enzyme-linked immunosorbent assay (ELISA), enzyme-linked immuno-spot assay (ELISPOT) and flow cytometry (FCM) in 27, 6 and 12 studies, respectively (Table 1 ), and some studies used several different assays for outcome measurement.…”
Section: Resultsmentioning
confidence: 99%
“…Criteria for patients with aTB were similar and mostly consistent across studies including culture confirmation and/or presence of acid fast bacilli in sputum smear. Two studies also used positive polymerase chain reaction results as confirmation of aTB ( 34 , 37 ). Further to this in 6/34 (18%) studies diagnosis of aTB was based on clinical criteria ( 20 , 34 , 37 , 40 , 50 , 51 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents and adults represent the primary target population for subunit TB vaccination (63). However, the immune response of adolescents is not often analyzed as a separate entity but merged with that found in either children (48,64) or adults (37). The need for carefully considering different age groups is supported by the M72/AS01E efficacy trial results, which showed that the highest vaccine efficacy in preventing active TB among LTBI was in individuals of 25 years of age or younger, after 2.5 years of follow up (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of tuberculosis in humans is also higher in children and older adults, albeit the clinical features tend to be distinct, probably as a consequence of the likewise distinct underlying immune response [116]. Nevertheless, in both these populations, Mycobacterium tuberculosis growth and active disease is predicted to be favored by an unbalance in the percentage of IFN-γ + CD4 + T lymphocytes recruited to the infection site [117][118][119][120]. These findings were further replicated in aged murine models of tuberculosis infection and ultimately match the postulated importance of IFN-γ in BU, which if not totally ablated by mycolactone, confers some degree of protection against M. ulcerans [43,47,115,121].…”
Section: Epidemiological Clues and The Search For Novel Resistance Anmentioning
confidence: 99%